« Nombre des hommes » et « populatio » à la fin de la Renaissance : notes sur la généalogie des savoirs démographiques - Luca Paltrinieri (Astérion)
In one of his lectures at the Collège de France, Foucault observed that, prior to the eighteenth century, ‘population’ was a ‘present-absent’ object in the theories and practices of government. In this paper, I have attempted to reconstruct the genealogical history of proto-demographic thought as reflected in the works of three major Renaissance political theorists: Niccolò Machiavelli, Jean Bodin, and Giovanni Botero. While all three thinkers address the question of how to cultivate a large and flourishing population, the primary obstacle to the emergence of a modern conception of population lies in the inability to influence human reproduction directly, an area traditionally regarded as subject to divine will.Botero, however, introduced the possibility of an ‘incentive’ policy, promoting marriage and child-rearing, which foreshadowed the natalist policies later advocated by Mercantilists. The case of ‘population’ and its peculiar ‘presence-absence’ in Renaissance political theories, as interpreted through Foucault’s hypothesis, sheds light on the broader history of scientific objects —objects that are neither ‘discovered’ nor ‘invented’, but rather acquire their reality gradually over centuries through political and scholarly debate.